Dynamics of protection against virulent challenge in swine vaccinated with attenuated African swine fever viruses - Carlson, Jolene Christine (Kansas State University, 2016)
African swine fever (ASF) is a lethal hemorrhagic disease of swine caused by a double-stranded DNA virus. ASFV is endemic in Sardinia and Saharan Africa and has been recently expanded from the Caucasus to Eastern Europe. There is no vaccine to prevent the disease and current control measures are limited to culling and restricted animal movement. Swine infected with attenuated strains are protected against challenge with a homologous virulent virus, but there is limited knowledge of the host immune mechanisms generating that protection. Swine infected with Pret4 virus develop a fatal severe disease, while a derivative strain lacking virulence-associated gene 9GL (Pret4Δ9GL virus) is completely attenuated. Swine infected with Pret4 Δ9GL virus and challenged with the virulent parental virus at 7, 10, 14, 21, and 28 dpi showed a progressive acquisition of protection (from 40% at 7 dpi to 80% at 21 and 28 dpi). This animal model was used to associate the presence of host immune response and protection against the challenge. Anti-ASFV antibodies and cytokines in serum, as well as ASFV-specific IFN-γ production in PBMCs, were assessed in each group. Interestingly, with the exception of ASFV-specific antibodies in the surviving swine challenged at 21 and 28 dpi, no solid association between any of the parameters assessed and the extent of protection could be established. These results were corroborated using a similar model based on the use of a rationally attenuated derivative of the highly virulent strain Georgia 2007. These results, encompassing data from 114 immunized swine, underscore the complexity of the system under study where it is very plausible that protection against disease or infection relies heavily on the concurrence and or interaction of different host immune mechanisms.
Keywords: African swine fever virus; Interferon gamma; Attenuated virus; Correlates of protection; Vaccination; 9GL